Estudio del desamargado por fermentación y lavado de dos ecotipos, dos variedades de chocho (Lupinus mutabilis sweet) y dos índices de madurez. - Sisalema Sánchez, Walter Rolando (2021)
The objective of this research was to carry out a study of debittering by fermentation and washing of two ecotypes, two varieties of lupine (lupinus mutabilis sweet) and two indices of maturity”, through this experimentation it was verified that the method of debittering by fermentation did not It is widely used, since in this type of method the Rhizopus Oligosporus fungus is used. To carry out this study, an experimental design was applied under an AxBxC factorial arrangement of a completely randomized block design (DBCA), with two replications and a total of 16 treatments; each factor with two levels; levels of factor A (Harvest time); a1: (tender) and a2: (dry), levels of Factor B (Varieties of lupine); b1: (INIAP 450 Andino) and b2: (INIAP 451 Guaranguito) and Factor C levels (Ecotypes of lupine); c1: (Native local ecotype) and c2: (Peruvian local 1 ecotype). The variables that were measured were pH, Humidity, ashes and alkaloids taken after obtaining the treatments under study. With the use of the statistical program Infostat, the analysis of the data obtained was carried out, where it was established that the best treatment was t7 (a2b2c1), obtaining that the physcochemical parameters obtained the following results: pH 6.54%, humidity 74.0 %, ash 2.50% and alkaloids 0.004%. These parameters are within the permissible limits stipulated by the (NTE INEN 2390, 2004) regulates that the grain of lupine debittered for human consumption must comply with the physcochemical parameters such as: humidity 72.00-75.00%, ashes 1, 9-2.50%, alkaloids 0.02-0.07%. While for the microbiological analyzes it was obtained that Molds and yeasts 4x 102 ufc/ cm3, total coliforms 10-102 NMP / g and Escherichia coli obtained absence. These parameters are within the permissible limits stipulated by the (NTE INEN 2390, 2004) regulates that the lupine grain debittered for human consumption must comply with the microbiological requirements: Total coliform count 10-102 MPN / g, mold count and yeasts 0-5 x 102 ufc/cm3 and Escherichia coli in the absence. A cost analysis of the best treatment of lupine debittered by fermentation was also developed, which indicates that to debitter 1kg of lupine by fermentation is feasible since it obtains a price of $ 8.01, in the same way a possible introduction in the market would be viable.